Cognitive impairment negatively impacts self-efficacy in patients with chronic heart failure patients: results from the Cognition.Matters-HF study. (3rd October 2022) - Wissel, S; Frey, A; Sell, R; Frantz, S; Stoll, G; Stoerk, S
Abstract: Background: Cognitive impairment is highly prevalent in patients with chronic heart failure (HF), but evidence on its relationship with health-related quality of life (HRQoL) is sparse. We aimed to examine whether cognitive impairment is associated with HRQoL. We hypothesized that cognitive impairment would negatively impact HRQoL. Methods: A total of 148 outpatients with chronic stable HF (mean LV ejection fraction 43±8%) were enrolled in the Cognition.Matters-HF prospective cohort study: mean age 64±11 years, 16% women, 77% in NYHA functional class I-II. Patients were extensively evaluated within 2 days by cardiological, neurological, and neuropsychological testing and brain magnetic resonance imaging (MRI). Severity of cognitive deficits were categorized based on the domains affected according to neurocognitive test battery results: 0 domains ("none", n=46 [31%]), 1–2 domains ("mild", n=77 [52%]), and >2 domains ("severe", n=24 [16%]). HRQoL was measured with the generic Short-Form 36 (SF-36) and the disease-specific Kansas City Cardiomyopathy Questionnaire (KCCQ). Multivariable analysis of variance and regression modelling were applied to model associations between cognitive impairment and HRQoL. Results: Cognitive impairment was not associated with overall scores of SF-36 and KCCQ nor any of the subscales, with the exception of the self-efficacy scale of the KCCQ. Self-efficacy represents the ability of patients to care for themselves; it quantifies a patient's unterstanding of how to prevent heart failure exacerbations and manage arising complications. Self-efficacy was negatively associated with cognitive impairment (beta=−0.242; p=0.004) and was rated 15% lower (B=−0.148) per increment in cognitive deficit category. The association of self-efficacy with cognitive impairment remained significant after adjustment for duration and severity of HF, age, and sex (p<0.001). Conclusions: With the exception of self-efficacy, the severity of cognitive impairment was not associated with lower HRQoL in patients with chronic HF. The self-efficacy scale of the KCCQ is a promising tool potentially suited to detect individuals, who are unable to adhere to a proper HF treatment regimen. These patients may benefit from enhanced care, e.g. in the frame of a HF nurse led management program. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): BMBF